Day 3 Wed, November 11, 2015 2015
DOI: 10.2118/177688-ms
|View full text |Cite
|
Sign up to set email alerts
|

Application of Enzyme EOR in a Mature UAE Offshore Carbonate Oil Field

Abstract: Total has been operating oil and gas production from a series of heterogeneous reservoirs offshore Abu Dhabi since 1974. One of the main oil producing reservoirs of Jurassic age has been the subject of a number of EOR studies at lab and field scale to achieve a higher ultimate recovery factor. In 1991, TABK initiated its first gas injection EOR Pilot with full-field expansion in 1997. In 2014 a successful Chemical EOR Pilot was carried out that showed a significant drop in residual oil saturatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 4 publications
1
6
0
Order By: Relevance
“…On the contrary, wettability alteration from weakly oil-wet/neutral-wet to more water-wet condition was hypothesised as one of the possible factors that militated against positive effect of enzyme EOR applications in three of the four wells in carbonate reservoir studied by Jabbar et al [27]. They however did not carry out any wettability investigations on the reservoir used in their study.…”
Section: Wettabilitymentioning
confidence: 90%
See 4 more Smart Citations
“…On the contrary, wettability alteration from weakly oil-wet/neutral-wet to more water-wet condition was hypothesised as one of the possible factors that militated against positive effect of enzyme EOR applications in three of the four wells in carbonate reservoir studied by Jabbar et al [27]. They however did not carry out any wettability investigations on the reservoir used in their study.…”
Section: Wettabilitymentioning
confidence: 90%
“…This further showed the capacity of enzymes to withstand high salinity and their efficiency in such salinity medium. Also in the enzyme EOR study carried out by Jabbar et al [27] on four carbonate wells with salinity range of 222,000 -247,300 ppm, they observed no difference in the behavior of the wells before and after it applications, which suggest its stability in that reservoir system.…”
Section: Salinity Effectmentioning
confidence: 94%
See 3 more Smart Citations